Immune Dysfunction in HIV: A Possible Role for Pro- and Anti-Inflammatory Cytokines in HIV Staging - Iorhen Ephraim Akase; Bolanle O. P. Musa; Reginald Onyedumarakwe Obiako; Abdurrahman Ahmad Elfulatiy; Abdullahi Asara Mohammed (Journal of Immunology Research)
HIV infection is a chronic infection that almost inevitably progresses to AIDS. The infection is characterized by the deterioration in the immune function leading to opportunistic infections and malignancies. Additionally, there is an associated immune dysfunction characterized by a persistent inflammatory state and unhealthy elaboration of both pro- and anti-inflammatory cytokines. The CD4+ T cell count has been used as a surrogate for the level of immune dysfunction that exists in patients with HIV infection. Eighty-eight (88) patients with HIV infection, forty-four (44) of whom were treatment naïve patients and forty-four (44) who were treatment-experienced patients, were recruited. The serum concentrations of cytokines IL-6 and IL-10 were carried out using R&D human Quantikine ELISA kits, while patients’ CD4+ T cell counts were evaluated using the Partec easy count kit. The serum IL-6 and IL-10 concentrations were significantly higher among the AR-naïve participants compared to the ART-experienced group. Additionally, the IL-6 and IL-10 concentrations were higher in patients with lower CD4+ T cell count compared to those with higher cell counts though this was not statistically significant. Also, both IL-6 and IL-10 concentrations were higher in patients with higher WHO clinical staging of disease, significantly so for IL-6.